2012
DOI: 10.1088/1742-6596/338/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

A new method of construction of all sets of mutually unbiased bases for two-qubit systems

Abstract: Mutually unbiased bases are an important tool in many applications of quantum information theory. We present a new algorithm for finding the mutually unbiased bases for two-qubit systems. We derive a system of four equations in the Galois field GF(4) and show that the solutions of this system are sufficient for obtaining the most general set of mutually unbiased bases. Further, our algorithm is applied to an example and we show that there are three possible solutions of the system of four equations, each solut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Theorem If (1) and (3) are MUMEBs for C d ⊗ C d , then the maximally entangled bases (11) and (12) are MUMEBs for C d ⊗ C d k .…”
Section: Construction Of Mumebs For C D ⊗ C D Kmentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem If (1) and (3) are MUMEBs for C d ⊗ C d , then the maximally entangled bases (11) and (12) are MUMEBs for C d ⊗ C d k .…”
Section: Construction Of Mumebs For C D ⊗ C D Kmentioning
confidence: 99%
“…Different constructions of MUBs, especially for prime power and partial qubits systems, have been presented in [12,13]. In [14] the authors first considered the unextendible maximally entangled bases and mutually unbiased bases.…”
Section: Introductionmentioning
confidence: 99%
“…A 1 is an extraordinary subgroup and A j = a j + A 1 with j = 2, 3, ..., d. The importance of the extraordinary subgroup is explained briefly in the Introduction, where we emphasized that the condition tr(x 1 y 2 − x 2 y 1 ) = 0 is equivalent to the commutation of two operators, whose associated elements are (x 1 , y 1 ) and (x 2 , y 2 ) in F d × F d [13], [5].…”
Section: Extraordinary Supersquaresmentioning
confidence: 99%
“…One main concern is about the maximal number of MUBs for given dimension d. It has been shown that the maximum number N (d) of MUBs in C d is no more than d + 1 [21] and N (d) = d + 1 if d is a prime power. Different constructions of MUBs, especially for prime power and qubits systems, have been presented in [33][34][35][36][37][38][39][40]…”
Section: Introductionmentioning
confidence: 99%